OP46 Tradition and Innovation: A qualitative study of changing maternal and newborn health practices in Ethiopia. (13th September 2016) - Mitchell, KR; Mathewos, B; Russell, J; Bekele, A; Schellenberg, J
Abstract : Background: Neonatal mortality in Ethiopia (37 per 1000 live births) is unacceptably high and explained primarily by high rates of home deliveries, lack of skilled attendants at birth and poor utilisation of health services. This study sought to understand how novel, 'outsider' knowledge contests traditional neonatal practices, and to identify factors that facilitate and constrain changes in behaviour. Methods: A qualitative process evaluation of ante- and postnatal visits by community volunteers and Health Extension Workers (HEWs), within the context of a cluster-Randomised Controlled Trial of community-based treatment of neonatal sepsis by HEW. Data from 23 focus group discussions with: project staff (5); community volunteers (6); fathers (6) and grand-mothers (6) of recently-born infants. 23 interviews with HEW (n = 11) and mothers of recently-born infants (12). Data analysed thematically. Results: Diffusion of innovation theory provides an explanatory framework to understand how novel ideas spread. It suggests that attributes of the novel behaviour – complexity, risks and benefits, trialability and visibility – determine the pace of change. Switching from home to health centre delivery required complexity in terms of forward planning and co-operation from others. Expectant mothers considered loss of privacy, comfort, respect and control as key risks to be weighed against the benefit of safer delivery. Delivery at a health centre could not be trialled (as it occurs only once in pregnancy) but journeys to the health centre were typically visible and experiences there were later discussed with neighbours. Communities worked to reconcile old customs with novel practices. For instance, HEWs were often excused from customary rules preventing non-family members from touching the newborn. Diffusion theory states that communication channels, time and the social system also affect the pace of change. HEWs and volunteers were viewed as key conduits of change, bringing advice and support to the door. Change was also facilitated by the broader social context in Ethiopia; participants perceived decreasing tolerance of the risks of childbirth; greater flexibility in gendered roles; changing normative attitudes towards neonates; and significant improvements in education and health care provision. Conclusion: The pace of change may be enhanced where communities are effectively supported to integrate old and new, in ways that do not denigrate the old. Community volunteers and health workers appear well placed to support this process. Diffusion of innovation theory provides a useful framework to understand the process of change and to identify ways to accelerate it.